Teaching Material Mathematics with a Metacognitive Approach Guidance - Arvyaty Arvyaty; Salim Salim; Era Maryanti (Journal of Education and Learning (EduLearn), 2018)
The purpose of this research is to analyze the improvement of students' mathematical literacy ability through the use of mathematics teaching materials with metacognitive approach guidance. This research will be held in the city of Kendari to the subject of this research target is students who are at grade 5 Land in Junior High VIIID Kendari years lessons 2017/2018 with many limited scale trial class is only required as much as 1 class. To know the significance of the increase in the literacy abilities of students using paired t-test. Data processing using the SPSS program with criteria if α=0,05 then there is an increased of student's mathematical literacy ability. The results of the analysis on the stages of the evaluation shows the learning materials with metacognitive approach guidance can provide better against an increase in student learning. The ability of the early mathematical literacy against students is very less because of learning during this time students have not been directed with the ability of mathematical literacy. After the students get learning by using learning materials through metacognitive approach guidance, the ability of mathematical literacy students’ level 3 and level 4 underwent significant improvement.